2018
DOI: 10.1021/acsnano.8b06758
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Optical Detection of DNA Translocations through Plasmonic Nanopores

Abstract: Solid-state nanopores are single-molecule sensors that hold great potential for rapid protein and nucleic-acid analysis. Despite their many opportunities, the conventional ionic current detection scheme that is at the heart of the sensor suffers inherent limitations. This scheme intrinsically couples signal strength to the driving voltage, requires the use of high-concentration electrolytes, suffers from capacitive noise, and impairs high-density sensor integration. Here, we propose a fundamentally different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 50 publications
6
129
0
Order By: Relevance
“…4b) and other independent measurements on bowtie nanoapertures. 37 We also probe two different gap sizes and find again similar temperature increases (Fig. 4g).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…4b) and other independent measurements on bowtie nanoapertures. 37 We also probe two different gap sizes and find again similar temperature increases (Fig. 4g).…”
Section: Resultssupporting
confidence: 59%
“…37 This value is lower than the one that we measure experimentally, we ascribe this difference to the presence of the titanium adhesion layer in our case, while no adhesion layer was used in ref. 37 Interestingly, this observation suggests new routes to tune the local temperature increase, which we are currently exploring. It should still be noted that the temperature increase in the presence of a continuous metal film 29 remains always significantly lower than for isolated structures such as nanoparticles 25 or nanoantennas.…”
Section: Resultsmentioning
confidence: 56%
“…Ploschner et al theoretically studied the optical forces exerted on glass nanobeads in the proximity of a gold nanoantenna and noted that the localization of the particles is due to heating effects, which probably dominate over optical forces [63]. Verschueren et al demonstrated a temperature increase of 3.6°C at metallic nanopore when illuminated with an incident power of 7.5 mW [64]. Xu et al predicted a maximum temperature increase of 6°C for double nanoaperture at an incident laser intensity of 6.67 mW/μm 2 [65].…”
Section: Advantages and Disadvantages Of Potmentioning
confidence: 99%
“…Near‐field focusing by the antenna of the incident optical field to a nanosized hotspot permits optical nanotweezing of small nano‐objects like single proteins, whereupon changes in the light transmitted through the antenna report on the presence of the object. The advantages that this all‐optical readout offers over traditional ionic‐current sensing are outlined elsewhere . Notably, the plasmonic nanopore chip separates two fluidic reservoirs in a custom‐made flow cell, which allows for a variable bias voltage to be applied across the membrane and an electrophoretic force to be acted on the object (see Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…The advantages that this all-optical readout offers over traditional ionic-current sensing are outlined elsewhere. [29,30] Notably, the plasmonic nanopore chip separates two fluidic reservoirs in a custom-made flow cell, which allows for a variable bias voltage to be applied across the membrane and an electrophoretic force to be acted on the object (see Experimental Section for details). Figure 1B shows a schematic of the optical nanoantenna, with the definition of various geometrical parameters indicated in the figure.…”
Section: Inverted-bowtie Plasmonic Nanopores For Optical Trappingmentioning
confidence: 99%